Selected topics in information technology : series 1 - Kassim, Shahreen (Penerbit UTHM, 2017)
This volume is devoted to the recent developments on Information and Communication Technology (ICT) systems and applications spread across various domain. It seeks to illustrate the potential of Information Technology for a wide range of applications via a systematic collection of recent methods, procedures, and applications designed to solve real-life problems. This book contains ten chapters that emphasize recent information technologies development. Each chapter has been carefully selected to represent a distinctive domain, each with its own unique theoretical, methodological, and empirical developments of solutions on different platforms. The content of this book is organized as follows: Chapter 1 models an assistive ICT solution for people with health concerns by monitoring the patients’ general well-being and medicine intake. In Chapter 2, a standard brick-and-mortar directory kiosk is transformed to allow a virtual walkthrough through an experiential approach. Chapter 3 details out a proof of concept for a monitoring system dedicated for air quality for upto-the-minute information that helps user optimize their decisions. Chapter 4 looks into tailoring human resource management system for home furnishing business. Apart from monitoring and management system, Chapter 5 presents a yet another management system but for facilitators in managing campus orientation programs. Chapter 6 and Chapter 7 are social systems for planning a wedding and marriage matchmaking. The online systems cater from pre-to post wedding, hence suggesting a complete chain of new business model. In Chapter 8, an online practical exam system focuses on one specific course for an undergraduate program at UTHM. Finally, Chapter 9 and Chapter 10 present interesting information systems for expecting mothers and a decision support system for promoting Korean skincare products online. The opportunities now afforded by ICT as deliberated in this book ensures that there is great potential to serve a wide range of audiences. The editors would like to thank chapters’ contributors for their valuable contributions to make this book a success. The edited research book would not have been possible without them.